The impact of sowing structure on proftability of family farms directed at the fnal production of fattened beef cattle - Saša Todorović; Nikola Filipović; Tamara Paunović (Ekonomika Poljoprivrede (1979), 2010)
Small and inadequately used estates of family farms limit the capacities of cattle production because of limited forage production which is the basis of farm economic sustainability. Insuffcient and inadequate use of soil resources leads to the decrease of their competitiveness which also results in the need of fnding more rational ways of their organization.